Water deprivation activates a glutamatergic projection from the hypothalamic paraventricular nucleus to the rostral ventrolateral medulla - Stocker, Sean D. (2006)
Elevated sympathetic outflow contributes to the maintenance of blood pressure in water-deprived rats. The neural circuitry underlying this response may involve activation of a pathway from the hypothalamic paraventricular nucleus (PVH) to the rostral ventrolateral medulla (RVLM). We sought to determine whether the PVH-RVLM projection activated by water deprivation is glutamatergic and/or contains vasopressin- or oxytocin-neurophysins. Vesicular glutamate transporter2 (VGLUT2) mRNA was detected by in situ hybridization in the majority of PVH neurons retrogradely labeled from the ipsilateral RVLM with cholera-toxin subunit B (CTB; 85% on average with regional differences). Very few RVLM-projecting PVH neurons were immunoreactive for oxytocin- or vasopressin-associated neurophysin. Injection of biotinylated dextran amine (BDA) into the PVH produced clusters of BDA-positive nerve terminals within the ipsilateral RVLM that were immunoreactive (ir) for the VGLUT2 protein. Some of these terminals made close appositions with tyrosine-hydroxylase-ir dendrites (presumptive C1 cells). In water-deprived rats (n=4), numerous VGLUT2 mRNA-positive PVH neurons retrogradely labeled from the ipsilateral RVLM with CTB were c-Fos-ir (16–40% depending on PVH region). In marked contrast, few glutamatergic, RVLM-projecting PVH neurons were c-Fos-ir in control rats (n=3; 0–3% depending on PVH region). Most (94 ± 4%) RVLM-projecting PVH neurons activated by water deprivation contained VGLUT2 mRNA. In summary, the majority of PVH neurons that innervate the RVLM are glutamatergic and this population includes the neurons that are activated by water deprivation. One mechanism by which water deprivation may increase the sympathetic outflow is the activation of a glutamatergic pathway from the PVH to the RVLM.